Perilaku Konsumen Pada Komunitas Selenoid Dalam Perspektif Teori Jean Baudrillard - Muhammad Sholahuddin Al Farras (Journal of Development and Social Change, 2025)
This research discusses consumer behavior in the analog photography community (Selenoid) in Surakarta, especially in the symbolic and emotional context, using Jean Baudrillard's theory. The problem studied is how the use of analog cameras in this community is more than just a practical need, but rather as a means of expression of identity and social status. The purpose of this research is to understand the consumption patterns of analog photography community members, as well as the role of analog cameras and their supporting equipment as symbols of identity and authentic experience. The method used is qualitative research with a phenomenological approach. The sample was taken by purposive sampling method from active members of the Selenoid community who regularly use analog cameras. Data collection was done through observation and in-depth interviews, with data validity using source triangulation. The results showed that consumptive behavior in this community is not only functional, but also symbolic and emotional. Analog cameras and their equipment serve as symbols of identity, social status, and authenticity. Based on Baudrillard's theory, these objects create simulacra, where symbolic values and authentic experiences are valued more than their technical functions, which strengthen personal identity and solidarity within the community as a response to the instantaneous digital culture.